2020
DOI: 10.4014/mbl.1912.12016
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antimicrobial Activity of Essential Oil Extracted from Eucalyptus citriodora Leaf

Abstract: Eucalyptus oil is a rich source of bioactive compounds with a variety of biological activities and is widely used in traditional medicine. Eucalyptus citriodora is cultivated for the production of essential oils. However, the mode of antibacterial action of essential oils from E. citriodora is not well-known. This study aimed to determine the chemical components, microbial inhibitory effect, and mechanism of action of the essential oil from E. citriodora. The oil was extracted from E. citriodora leaves by hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Although E citriodora essential oil has not been studied for its antiviral effect, previous studies have reported its antifungal and antimicrobial properties. 27,28 It was demonstrated in previous antiviral studies that citronellal may be the compound responsible for bioactivity. 29,30 The antimicrobial and antiviral effects of citronellal-rich essential oils were significant, especially against HSV-type viruses.…”
Section: Resultsmentioning
confidence: 99%
“…Although E citriodora essential oil has not been studied for its antiviral effect, previous studies have reported its antifungal and antimicrobial properties. 27,28 It was demonstrated in previous antiviral studies that citronellal may be the compound responsible for bioactivity. 29,30 The antimicrobial and antiviral effects of citronellal-rich essential oils were significant, especially against HSV-type viruses.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, C. citriodora is reported to have antimicrobial properties (ESTANISLAU; BARROS; PEÑA, 2001, MAHMOUD;EBRAHIM;ALY, 2004, MISSANJO;MKWEZALAMBA, 2016, MUHAMMED;DADA;ALO, 2018, MIGUEL et al, 2018CHAHOMCHUEN, 2020), insecticide (NEGRINI et al, 2018) and anthelmintic (ARAÚJO-FILHO et al, 2019). According to Mulyaningsih et al (2011), some active and bactericidal compounds present in lemonscented gum essential oil are aromadendreno, 1,8-cineol, citronellal and citronellol, which explains the potential for inhibiting Xanthomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial principles (ESTANISLAU; BARROS; PEÑA, 2001, MAHMOUD; EBRAHIM; ALY, 2004, MISSANJO;MKWEZALAMBA, 2016, MUHAMMED;DADA;ALO, 2018, MIGUEL et al, 2018CHAHOMCHUEN, 2020. ), insecticides (NEGRINI et al, 2018) and anthelmintic (ARAÚJO-FILHO et al, 2019) have already been described in this species.…”
Section: ________________________________________________________________________________ Introductionmentioning
confidence: 99%
“…Thus, our data suggest a possible relationship between essential oil chemical components and species. The chemical composition of EOs can vary depending on the species, leaf age, harvesting period, geographical location, and extraction procedures (Siramon et al, 2013;Sebei et al, 2015;Barbosa et al, 2016;Lingan, 2018;Salem et al, 2018;Almasa et al, 2019;Insuan and Chahomchuen, 2020). The difference in chemical constituents of EOs is related to a difference in biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…The Eucalyptus leaf essential oils (EOs) were dried with anhydrous sodium sulphate and stored in glass vials at -20°C and protected from light until use. The identification of volatile constituents was performed using a GCMS-QP2010 apparatus (Shimadzu, Kyoto, Japan) and a ZB-WAX plus capillary column (30 m x 0.25 mm, 0.25 µm film thickness; Zebron, CA, USA) and a method was modified from Insuan and Chahomchuen (2020). GC-MS was carried out using split injection (split ratio 1:50) for a 0.2 µL oil sample, with the following temperature settings: injector set at 230 °C, column set at 60°C, heating ramp of 5°C/min, final temperature of 230°C, and detector set at 250°C.…”
Section: Extraction Of Essential Oils and Gas Chromatography-mass Spectrometry (Gc-ms) Analysismentioning
confidence: 99%